Indonesian Capital Market Investors' Reaction To The Events At Bank Syariah Indonesia - Carolin, Yohana (JPS (Jurnal Perbankan Syariah), 2024)
This study aims to analyze whether there are differences in internal and external events in abnormal profits, trading volume activity, and foreign investment in the stock market for BRIS issuers since the merger announcement and the ratification of the Bank Syariah Indonesia merger. This study is quantitative, where the data processed is secondary data from various sources. Several events during the merger period were collected from October 2020 to February 2021, and 11 events were obtained. This study divides the events into two groups and tests 5 internal and 6 external events with an event window of 11 days. The method used in this study is a different test using the Wilcoxon sign rank test and sample paired t-test, depending on the normal test results. The results of group testing events show no difference before and after internal and external events in abnormal profits, trading volume activity, and foreign investment. However, when viewed from each event, the results show that trading volume activity in events 1, 7, and 11 differs before and after. For foreign investment in events 7 and 11, there are differences before and after; for the rest, there is no difference. This research can provide insight and be a reference for future research. Practically, this research can be a reference for investors when determining investment decisions.